Application of Plating Principles on Indonesian Traditional Food Menu at Harris Hotel Kuta Restaurant, Bali - Prenata, Putu Putra; Prayogi, Putu Agus; Putri, Ida Ayu Karina (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
The development of culinary arts in the hospitality industry has made food plating  a critical factor in shaping the dining experience and reflecting the cultural identity of traditional cuisine. This study aims to analyze the application of plating  principles on Indonesian traditional food menus at Harris Hotel Kuta Restaurant, Bali; identify the challenges encountered in the implementation; and describe the solutions applied to overcome them. A qualitative descriptive approach was employed, with data collected through direct observation of the plating  process, semi-structured interviews with the Head of F&B Department and Head Chef, and documentation during January–May 2025. The results show that plating  principles including color balance, composition, garnish use, plate cleanliness, and presentation consistency have been systematically applied by kitchen staff. The traditional Indonesian menus, including nasi goreng, sate ayam, ayam betutu, and mie goreng, are presented with modern plating  techniques that preserve the original taste and cultural identity while enhancing visual appeal. Challenges identified include time constraints during peak hours, simultaneous incoming orders, and maintaining consistent presentation across different staff members. Solutions implemented include strengthening team communication, applying standard plating  guidelines and standardized recipes, and collaborative teamwork. This study concludes that systematic plating  application enhances dining experience quality, elevates the restaurant's image, and effectively promotes Indonesian traditional cuisine to both domestic and international tourists.